Distribution of IgG subclass anti-nuclear antibodies (ANAs) in systemic lupus erythematosus. (May 2021) - Zeng, Yanli; Zhang, Yan; Chen, Qinggui; Huang, Qinghe; Lin, Yiqiang; Wang, Xuelian; Wang, Jia Jia; Jiang, Longcan; Xiao, Yun
Objectives: Our study purpose was to detect the distribution of anti-nuclear antibody (ANA) IgG subclasses in patients with systemic lupus erythematosus (SLE) and to evaluate their influence on the inflammatory process in SLE. Methods: We determined the serum levels of ANA IgG subclasses from 70 SLE patients, 25 patients with other autoimmune diseases (OAD), and 25 healthy controls using ELISA. The serum level of total ANA IgG and the avidity of ANA IgG, dsDNA IgG, and dsDNA IgG subclasses were analysed by ELISA. Results: The results indicated that levels of four ANA IgG subclasses (IgG1, IgG2, IgG3 and IgG4) and total IgG were significantly higher in SLE patients than in OAD patients and healthy controls ( p < 0.001). Moreover, the level of each ANA IgG subclass and the prevalence of high-avidity IgG ANAs (HA IgG ANAs) were significantly higher in the active cases than in the inactive cases of SLE and LN. Furthermore, level of ANA IgG subclasses decreased as level of dsDNA IgG subclasses decreased in 30 patients with SLE. In comparison, ANA IgG3 was significantly effective in high-dose prednisone combined with hydroxychloroquine ( p = 0.025). Additionally, it revealed that level of dsDNA IgG had a significant influence on four ANA IgG subclasses, especially on ANA IgG3 (β coefficient = 0.649, p < 0.001). Level of ANA IgG3 was also positively related to the serum level of dsDNA IgG (r = 0.729, p < 0.001 ) and RAI of HA IgG ANAs (r = 0.504, p < 0.001 ). However, the level of ANA IgG4 was positively related to the serum level of albumin (r = 0.572, p < 0.001 ) and RAI of HA IgG ANAs (r = 0.549, p < 0.001 ). Moreover, the results revealed that cutaneous and renal involvement were mainly associated with the ANA IgG1 and IgG4 subclasses. Although, arthritic involvement was mainly associated with ANA IgG3. Conclusions: First, we demonstrated that the ANA IgG subclasses were diagnostic tools in SLE patients. Furthermore, HA IgG ANAs might affect the distribution of ANA IgG3 and IgG4. Moreover, ANA IgG3 might play a particular role in the activity of SLE disease and therapy. Therefore, an altered ANA IgG subclass distribution might be a risk factor influencing the inflammatory process in SLE.